Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1210/jc.2002-021545
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Exendin-4 (Exenatide) Significantly Reduces Postprandial and Fasting Plasma Glucose in Subjects with Type 2 Diabetes

Abstract: Despite the advent of new treatments, glucose control in the type 2 diabetes population is unsatisfactory. AC2993 (synthetic exendin-4; exenatide), a novel glucose-dependent insulinotropic agent, exhibited notable antidiabetic potential in two clinical studies in patients with type 2 diabetes. In study A, 24 subjects received sc injections of study medication (0.1 micro g/kg AC2993 or placebo) twice daily with meals for 5 d. Statistically significant reductions in mean postprandial circulating concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
400
3
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 510 publications
(427 citation statements)
references
References 36 publications
18
400
3
6
Order By: Relevance
“…13,14 The principal result of this insulinotropic effect is an acceleration of glucose disappearance into peripheral tissues. Exenatide additionally limits glucose appearance via glucose-dependent slowing of gastric emptying 15,16 and suppression of inappropriately elevated postprandial glucagon secretion. [15][16][17] More recently, exenatide has been found to promote pancreatic b-cell proliferation and islet cell neogenesis in both animal and in vitro studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 The principal result of this insulinotropic effect is an acceleration of glucose disappearance into peripheral tissues. Exenatide additionally limits glucose appearance via glucose-dependent slowing of gastric emptying 15,16 and suppression of inappropriately elevated postprandial glucagon secretion. [15][16][17] More recently, exenatide has been found to promote pancreatic b-cell proliferation and islet cell neogenesis in both animal and in vitro studies.…”
Section: Introductionmentioning
confidence: 99%
“…Exenatide additionally limits glucose appearance via glucose-dependent slowing of gastric emptying 15,16 and suppression of inappropriately elevated postprandial glucagon secretion. [15][16][17] More recently, exenatide has been found to promote pancreatic b-cell proliferation and islet cell neogenesis in both animal and in vitro studies. 18,19 In addition to its role in glycemic control, GLP-1 is a shortterm regulator of food intake, [20][21][22] an effect mediated via central GLP-1 receptors.…”
Section: Introductionmentioning
confidence: 99%
“…While both basal insulin and incretin therapies effectively reduce fasting glucose levels, incretin therapies also reduce PPG 17 and glucagon 18. Studies in patients with Type 1 diabetes have shown that GLP‐1RAs can improve glycaemic control even among those with little to no β‐cell function, suggesting that glucagon control may be particularly influential in those with long‐term Type 2 diabetes 19.…”
Section: Incretin Effect and The Role Of Glucagonmentioning
confidence: 99%
“…This is also true for other incretin mimetics, such as exenatide [17] and liraglutide [18]. It should be noted that a decrease in the rate of gastric emptying has not been observed in clinical studies on DPP-IV inhibitors [19].…”
Section: Dpp-iv Inhibitors Have Little Effect On Gastric Emptyingmentioning
confidence: 99%
“…GLP-1 has glucose-lowering effects, both during and after its administration [1], as do incretin mimetics such as exenatide and liraglutide [17,18]. Based on the assumption that the effects of DPP-IV inhibition are mediated by GLP-1, one might expect that the maximum clinical effectiveness of inhibition would be reached within a few hours.…”
Section: Dpp-iv Inhibition Has Delayed Effects On Glucose Homeostasismentioning
confidence: 99%